2016
DOI: 10.18632/oncotarget.12715
|View full text |Cite
|
Sign up to set email alerts
|

FAM83D associates with high tumor recurrence after liver transplantation involving expansion of CD44+ carcinoma stem cells

Abstract: To investigate the potential oncogene promoting recurrence of hepatocellular carcinoma (HCC) following liver transplantation (LT), throughput RNA sequencing was performed in a subgroup of HCC patients. The up-regulated FAM83D in HCC tissues was found and further verified in 150 patients by real-time PCR and immunohistochemistry. FAM83D overexpression significantly correlated with high HCC recurrence rate following LT and poor HCC characteristics such as high AFP, poor differentiation. Of cancer stem cells (CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
6
13
0
Order By: Relevance
“…Therefore, these two genes might have better predictive ability to identify HCV-HCC at early stage on the background of HCV-cirrhosis. Consistent with our nding, CDKN3 and FAM83D were important regulators of cell cycle, and studies had also shown that they were highly expressed in tumor tissues compared to normal tissues, and overexpression of CDKN3 and FAM83D was correlated with the poor outcome in HCC patients [24,[29][30][31][32][33]. However, studies focusing on the role of these two genes in HCV-HCC occurrence and progression on the background of HCV-cirrhosis are limited.…”
Section: Disscusionsupporting
confidence: 86%
“…Therefore, these two genes might have better predictive ability to identify HCV-HCC at early stage on the background of HCV-cirrhosis. Consistent with our nding, CDKN3 and FAM83D were important regulators of cell cycle, and studies had also shown that they were highly expressed in tumor tissues compared to normal tissues, and overexpression of CDKN3 and FAM83D was correlated with the poor outcome in HCC patients [24,[29][30][31][32][33]. However, studies focusing on the role of these two genes in HCV-HCC occurrence and progression on the background of HCV-cirrhosis are limited.…”
Section: Disscusionsupporting
confidence: 86%
“…ALDH1 activation and high CD44 expression have also been reported as markers to identify cell populations enriched for CSCs in breast cancer, gastric cancer and lung cancer . In general, only a minority of cells (<5%) in the total tumour cell population are believed to be stem cells, but the flow cytometric analysis of several studies revealed that the percentage of cells expressing CD133, CD44 or ALDH1 differed between several HCC cell lines (from <1% to more than 90%) . In our study, the results shown in Figure indicate that more cells with high CPA4 expression expressed stem cell markers; more Bel7402 cells expressed stem cell markers than HepG2 cells.…”
Section: Discussionsupporting
confidence: 60%
“…28 In general, only a minority of cells (<5%) in the total tumour cell population are believed to be stem cells, but the flow cytometric analysis of several studies revealed that the percentage of cells expressing CD133, CD44 or ALDH1 differed between several HCC cell lines (from <1% to more than 90%). [29][30][31] In our study, the results shown in Figure 3 indicate that more cells with high CPA4 expression expressed stem cell markers; more Bel7402 cells expressed stem cell markers than HepG2 cells. Transfection with CPA4 plasmids increased stem cell marker expression, indicating that CPA4 may induce the proportion of stem cell marker-expressing cells.…”
Section: Discussionsupporting
confidence: 53%
“…CD44/CD24 has been reported to drive CSC progression in different cancer types [26] , [27] , [28] . We detected the influence of BPTF on their expression level in HCC cells.…”
Section: Resultsmentioning
confidence: 99%